Determining Enablers of Technology Adoption in Unorganized Localized Retail Outlets in India: A Technology Acceptance Model (TAM) Approach - Ahmad, Irfat; Dixit, Shailja; Siddiqui, Masood; Sharma, Praveen Kumar; Verma, Sapna; Mishra, Manish (International Review of Management and Marketing, 2025)
Digital transformation has changed customer expectations and behaviours leading to increased pressure on traditional businesses and disrupting the markets. The Indian retail market which is the third largest in Asia and fourth largest in the world majorly consists of the unorganised sector predominantly due to the presence of local stores and vendors with characteristic of low capital investment, family ownership, heavy dependence on cash transactions. The e-commerce platform and the emergence of phygital technologies are posing threat to the existence of these retail stores. To prevent such vulnerabilities, it is vital for small retailers to digitise their sales and business operations for survival. This study focused on the identification of the enabler’s technological adoption in unorganized small localized unorganized Kirana stores. A theoretical model was constructed with certain modifications based on technology adoption models: Technology Acceptance Model (TAM) and to understand the pertinent factors impacting the intention of retailers for technology adoption. Through survey method, the data was collected from 603 Unorganized Localized Retail Outlets Stores from different regions of India and the theoretical model was validated. Specifically, perceived trust emerged as a crucial factor in fostering positive attitudes toward technology adoption. Furthermore, the model explained a substantial proportion of variance in behavioural intention, highlighting the importance of addressing trust and usability concerns to facilitate Technological adoption. The study significantly adds value to the scant literature available before the era of phygital.